Experimental investigation of forced and mixed convection heat transfer in a foam-filled horizontal rectangular channel - Kurtbas, Irfan; Celik, Nevin (Pergamon-Elsevier Science Ltd, 2009)
An experimental study was performed to investigate the heat transfer characteristics of the mixed convection flow through a horizontal rectangular channel where open-cell metal foams of different pore densities (10. 20 and 30 PPI) were situated. A uniform heat flux was applied at all of the bounding walls of the channel. For each of three values of the uniform heat flux, temperatures were measured on the entire surfaces of the walls. Results for the average and local Nusselt numbers are presented as functions of the Reynolds and Richardson numbers. The Reynolds number based on the channel height of the rectangular channel was varied from 600 to 33000, while the Richardson number ranged from 0.02 to 103, extending over forced, mixed and natural convection. Second important parameter that influences the heat transfer is the aspect ratio of the foams. Three different aspect ratios (AR) as 0.25, 0.5 and I are tested. Based on the experimental data, new empirical correlations have been constructed to link the Nusselt number. The results of all cases were compared to that of the empty channel and the literature. We found that our results were in agreement with those that are mentioned in the literature. (C) 2009 Published by Elsevier Ltd.
Keywords: Metal foams; Mixed convection; Porous media; Rectangular channel flow